Evaluation of In‐House Loop‐Mediated Isothermal Amplification (LAMP) Assay for Rapid Diagnosis of M. tuberculosis in Pulmonary Specimens. Issue 4 (12th July 2013) - Sethi, Sunil Kumar; Singh, Sumeet; Dhatwalia, Sunil Kumar; Yadav, Rakesh; Mewara, Abhishek; Singh, Malkit; Tewari, Rupinder; Sharma, Meera
<x xml:space="preserve">Abstract</x> Background Loop‐mediated isothermal amplification (LAMP) assay has come forward as a rapid, cost‐effective molecular technique for diagnosis of tuberculosis (TB) in developing countries. This study evaluated Mycobacterium tuberculosis–specific in‐house LAMP assay targeting 16s rRNA and compared it with other conventional tests and nucleic acid amplification assay (IS6110 PCR). Methods A total of 133 sputum specimens (103 from suspected pulmonary TB cases and 30 from non‐TB controls) were subjected to conventional tests, IS6110 PCR and 16s rRNA LAMP assay. Results Of the 103 patients, the maximum number of cases were found to be positive by LAMP assay, that is, in 87 (84.5%) patients, followed by culture positive in 78 (75.7%), IS6110 PCR in 74 (71.8%), and smear positive in 70 (67.9%) patients. Of the 83 smear positive and/or culture positive cases, LAMP detected 77 (92.77%) cases, and was found to be superior to IS6110 PCR, which could detect 69 (83.1%) cases; a concordance of 0.6 was obtained between the two tests using kappa statistics. Conclusion Overall, LAMP was simple and efficacious for early diagnosis of smear positive, culture positive cases as well as for confirmation of smear negative, culture negative cases, and was found to be superior to IS6110 PCR.